Numerical simulation and analysis of the transition to turbulence in boundary layer flows - Tong, Hok Yee. (2013)
The aim of this paper is to strengthen and validate the theory proposed by Vladimir V. Kulish, where the fluctuations of velocity during a laminar-turbulent transition can be viewed as a fractal time series [4]. The FRATSAN program which was written by Karthik Seetharaman was used as a means to analyze the multifractal time series by generating the Fractal Dimensions, Jeffreys Divergence Measure and Hurst Exponent values through the interpretation of the fluctuating velocity data [3]. Velocity data from the Open Channel Flow experiment and the Boundary Layer Flow experiment were re-analyzed again and the results were compared and reviewed. The eventual outcome had shown encouraging signs and reflected positive results. This implies that multifractal time series analysis carries a very high potential in predicating the transition from laminar to turbulent flow.